Real-world outcomes of prophylactic cranial irradiation utilization and efficacy for patients with extensive-stage small cell lung cancer treated with consolidative thoracic radiotherapy - Abdul H. Lone; Rohan Salunkhe; Vijithan Sugumar; Luna J. Zhan; Xiang Y. Ye; Andrea Bezjak; John Cho; Meredith E. Giuliani; Andrew J. Hope; Alexander Sun; Srinivas Raman; Penelope A. Bradbury; et al. (Clinical and Translational Radiation Oncology)
Background: The role of prophylactic cranial irradiation (PCI) is not well-defined in extensive-stage SCLC (ES-SCLC), with conflicting results from randomized trials and a lack of relevant data for patients who received consolidative thoracic radiotherapy (CTRT). We sought to evaluate the impact of PCI on the outcomes of ES-SCLC patients who were all treated with CTRT. Methods: A retrospective analysis of ES-SCLC patients without brain metastases who were all treated with CTRT between 2013–2021 at our institution was conducted. Overall survival (OS) and incidence of brain failure (BFR) were estimated using Kaplan-Meier estimation and cumulative incidence function. Multivariable Cox or Fine-Gray’s proportional hazard regression analysis (MVA) were performed to determine association between PCI and OS. Results: 47 patients met inclusion criteria and were theoretically eligible for PCI, 27 (57.4 %) received PCI and CTRT while 20 (42.6 %) received CTRT alone. Baseline characteristics were similar except for age, where patients receiving PCI were younger (median age 62) compared to patients who did not receive PCI (median age 72). Median OS with PCI was 19.2 months, compared to 10.8 months without PCI (P = 0.0334). This improved OS remained apparent in patients who received post-chemotherapy MRI restaging (P = 0.0245). BFR was reduced with PCI (HR = 0.22 [0.09–0.52], P = 0.0004). On MVA, PCI was significantly and independently associated with improved OS (HR = 0.39 [0.19–0.80], P = 0.01) and reduced BFR (HR = 0.20 [0.09–0.44], P = < 0.001). Conclusion: This real-world study found PCI was independently associated with improved OS and reduced BFR in ES-SCLC patients treated with CTRT compared to patients treated with CTRT not receiving PCI, including after post-chemotherapy brain MRI. The role of PCI with CTRT should be evaluated in prospective studies.